2016
DOI: 10.5897/ajb2016.15482
|View full text |Cite
|
Sign up to set email alerts
|

Somatic embryogenesis from zygotic embryos and thin cell layers (TCLs) of Brazilian oil palm (Elaeis guineensis Elaeis oleifera)

Abstract: Oil palm hybrid BRS Manicoré is important for plantations in the north of Brazil, as it is resistant to fatal yellowing and is compact. Seed germination is slow and reduced, so somatic embryogenesis is a promising alternative for its propagation. Two kinds of starting explants were used: Zygotic embryos (ZE) and thin cell layers (TCL) from the base of seedling aerial parts. Two culture medium formulae were compared (Y3 and modified MS), and several growth regulators (2,4-D, Picloram, BA, 2iP), putrescine and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Several studies has also been reported regarding the usage of 2.4-D in micropropagation of oil palm. The usage of zygotic embryos as explants sources produced the highest somatic embryos formation from callus grown on Y3 medium without or low concentration of 2.4-D [14]. The induction of somatic embryos in immature oil palm inflorescences of the pisifera palm occurred at a concentration of 500 μM 2,4-D [15].…”
Section: The Effect Of 24-d and Naa On Somatic Embryos Formationmentioning
confidence: 99%
“…Several studies has also been reported regarding the usage of 2.4-D in micropropagation of oil palm. The usage of zygotic embryos as explants sources produced the highest somatic embryos formation from callus grown on Y3 medium without or low concentration of 2.4-D [14]. The induction of somatic embryos in immature oil palm inflorescences of the pisifera palm occurred at a concentration of 500 μM 2,4-D [15].…”
Section: The Effect Of 24-d and Naa On Somatic Embryos Formationmentioning
confidence: 99%
“…This callogenesis frequency of OxG hybrid was comparable to that of E. guineensis at 15% [8] or 11-20% [12] and another OxG hybrid at 11.25% [7]. Callogenesis frequency of OxG hybrids using zygotic embryos was very high at 77.9-95.3% after 90 days on Brazilian OxG hybrids [4] and at 10-60% after 6 months on other Brazilian OxG hybrids [6]. Activated charcoal at 0.25% was used to reduce oxidation in the culture of zygotic embryos of OxG hybrids [13].…”
Section: Callus Initiationmentioning
confidence: 99%
“…In vitro propagation of OxG hybrids through somatic embryogenesis (SE) has been reported mostly using zygotic embryos as explants [4,5,6], but SE in OxG hybrids from young leaf explants has been reported only by Ginting et al [7] using one OxG hybrid on solid media. However, SE with young leaves as explants has been widely used in E. guineensis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that protocols for plant regeneration by SE in tree species are challenging for the mass propagation of these plants [28]. Several strategies have been used to develop protocols for obtaining somatic embryos from TCLs in tree species [29,30]. Thus, there is a need to increase knowledge of SE in each tree species to increase the availability of plants for use in reforestation programs.…”
Section: Summary Of Tcl Applications On Tree Speciesmentioning
confidence: 99%